Apakah Profitabilitas Memediasi Pengaruh Manajemen Modal Kerja terhadap Nilai Perusahaan? - Evan Yulandreano; Apriani Dorkas Rambu Atahau; Imanuel Madea Sakti (Postgraduate Program Merdeka University, 2020)
This study aims to examine the effect of working capital management on firm value with profitability as a mediating variable. This study uses a sample of 18 retail companies listed on the Indonesia Stock Exchange from 2014 to 2018. Working capital management is measured by Cash Conversion Cycle (CCC), profitability is measured by Return on Assets (ROA), and company value is measured by Tobins Q. Panel data regression is conducted to test the direct effect, followed by the Sobel test to test for the indirect effect. The results showed that working capital management increased firm value directly and indirectly through profitability. Working capital management with a shorter cycle results in greater profitability, thus driving firm value. The implication of this research is that retail companies are expected to shorten the company's cash cycle so that it has a positive impact on the company's profitability and value. DOI: https://doi.org/10.26905/afr.v3i2.5452